Dare to Compare. Development of Atherosclerotic Lesions in Human, Mouse, and Zebrafish - Vedder, Viviana L.; Aherrahrou, Zouhair; Erdmann, Jeanette (Frontiers in Cardiovascular Medicine, 2020)
Cardiovascular diseases, such as atherosclerosis, are the leading cause of death worldwide. Although mice are currently the most commonly used model for atherosclerosis, zebrafish are emerging as an alternative, especially for inflammatory and lipid metabolism studies. Here, we review the history of in vivo atherosclerosis models and highlight the potential for future studies on inflammatory responses in lipid deposits in zebrafish, based on known immune reactions in humans and mice, in anticipation of new zebrafish models with more advanced atherosclerotic plaques.